How ChatGPT Supports Students in Learning English: A Qualitative View - Arini Nabilla Dzulfahmi; Wardatul Abyadiyah; Naila Fatina Zuhriana; Kayla Ikhsania Fitriani; Aina Salsabila; Dewi Puspitasari (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
The incorporation of artificial intelligence (AI) into the educational sector has opened up fresh possibilities for English as a Foreign Language (EFL) learning, with ChatGPT emerging as a popular tool due to its interactive and immediate support. This qualitative study explored how ChatGPT supports students in learning English by examining their interaction patterns, the types of support provided, and their perceptions of its usefulness. Information was gathered by conducting semi-structured interviews with three individuals chosen intentionally undergraduate students who had substantial experience using ChatGPT to support their English learning. The participants were chosen because they could provide rich, comprehensive understandings of the topic being studied. The information gathered from interviews was later examined through thematic analysis.The findings revealed that students interacted with ChatGPT in different ways, ranging from active engagement through prompt refinement and follow-up questions to direct use for obtaining quick answers. ChatGPT provided linguistic, cognitive, affective, and practical support, and participants perceived it as a flexible and helpful learning tool that promoted independent learning. However, concerns regarding information accuracy and the risk of over-reliance were also identified. Overall, ChatGPT shows strong potential to support EFL learning when used critically and responsibly.